(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
People with active implantable medical devices today are a growing category, due to the increase of health care interventions that replace or remedy physiological deficiencies with intelligent artificial medical solutions. These devices are built with electronic circuits, susceptible to electromagnetic interference that could affect their proper operation and could cause discomfort or even health damage to the patient. Manufacture of medical devices has been regulated for decades by international technical standards (such as IEC 60601-1-2 or ANSI / AAMI PC69 series), including immunity conditions; however, attention must always be paid to the continuous assessment of the electromagnetic environment enriched with new technologies, in order to harmonize the sensitivity of health care devices and the possible conditions of uncontrolled human exposure. In this context, the authors present an attempt to evaluate the current protection offered to bearers of implantable devices in the electromagnetic environment specific to modern electric vehicles and especially to those using wireless power transfer systems for battery charging, due to the magnetic leakage field. These specific exposure conditions and particular regulations are investigated and compared with some assessments performed on the Dacia Electron electric vehicle.